Lobectomy may be more appropriate for patients with early-stage medullary thyroid cancer older than 60 years old - Yang, Binfeng; Niu, Guangcai; Li, Xiaoxin; Ma, Fenfen; Ma, Yanhong; Hu, Shaojun (Frontiers in Endocrinology, 2022)
Purpose: Clinical guidelines presently recommend total thyroidectomy for the treatment of medullary thyroid cancer (MTC). This study was aimed to investigate whether lobectomy could be the initial treatment for stage I MTC patients. Methods: The retrospective study was based on data from the Surveillance, Epidemiology, and End Results (SEER) database between 2004 and 2015. The risk factors of survival were estimated by the univariate and multivariate Cox proportional-hazards model. The effect of age on death risk was estimated using restricted cubic splines. Survival curves were constructed according to the Kaplan–Meier method. Results: A total of 988 stage I MTC patients was included in the study. Among them, 506 (51.2%) MTC patients received lobectomy and 482 (48.8%) received total thyroidectomy. The only independent prognostic factor for overall survival (OS) and disease-specific survival (DSS) was age, according to univariate and multivariate Cox regression analysis. The hazard ratio (HR) increased relatively slowly with age growing under the age of approximately 60 years. However, the death risk of MTC patients began to rise sharply with increasing age above 60 years. For patients under the age of 60, a significant survival difference for OS and DSS was observed between the lobectomy group and total thyroidectomy group (p < 0.05). However, for patients aged above 60, no significant survival difference was observed for OS or DSS (p > 0.05). Conclusion: Total thyroidectomy was an appropriate treatment for stage I MTC patients under the age of 60, which was consistent with the recommendation of the clinical guidelines. However, for those over the age of 60, lobectomy may be explored as a better surgical option. The findings may provide the evidence base for improving the clinical management of stage I MTC patients. Further prospective multicenter clinical studies are needed including information regarding RET status as well as calcitonin and CEA levels.